2006
DOI: 10.1002/rcm.2712
|View full text |Cite
|
Sign up to set email alerts
|

Ionization energies of LinX (n = 2, 3; X = Cl, Br, I) molecules

Abstract: Molecules of Li(n)X (n = 2, 3; X = Cl, Br, I) were examined with a magnetic sector mass spectrometer by surface ionization using a triple rhenium filament impregnated with fullerene (C60). The ionization energies obtained for Li(2)Cl, Li(2)Br and Li(2)I molecules are 3.8 +/- 0.1, 3.9 +/- 0.1 and 4.0 +/- 0.1 eV, respectively. The first ionization energy of Li(2)Cl is documented, while there are no literature data for the ionization energies of Li(2)Br and Li(2)I. The molecules of Li(3)Cl, Li(3)Br and Li(3)I wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
2
28
0
1
Order By: Relevance
“…[42] The values of the ionization energies of Li n Cl, n = 2-6, vary only slightly, indicating that an increase in the number of lithium atoms from 2 to 6 in these clusters does not affect their IE.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…[42] The values of the ionization energies of Li n Cl, n = 2-6, vary only slightly, indicating that an increase in the number of lithium atoms from 2 to 6 in these clusters does not affect their IE.…”
Section: Resultsmentioning
confidence: 95%
“…It was observed that the presence of C 60 on the ionizing Re filament is necessary for obtaining these clusters. [42] In the present study, clusters of the type Li n Cl (n = 2-6) were obtained by evaporating only the lithium chloride salt, meaning that the experimental setup in Fig. 1 presents a simpler way of forming very small lithium monochloride clusters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong bonding interactions among the alkali metal "ligands" (L) which help to offset the octet-ruleviolating structure and antibonding L-M interactions are believed to be the major contributions to both the structure and stability of these species [1,[6][7][8][9][10][11][12][13][14][15][16]. Since the first evidence of the Li 3 O molecule in 1978 [11], a number of lithium and other alkali metal containing compounds with unusual stoichiometries (e.g., Li 4 O, Li 5 O, Li 2 Cl, Li 2 F, Li 6 C, Na 3 O, Na 4 O) have been studied theoretically and experimentally [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The most prominent examples of superalkalies are small (i.e., triatomic) alkali metal clusters and hyperalkali molecules ML k+n with n=1 which are characterized by the lowest IPs (i.e., Li 3 4.11 eV vs. Li 4 4.74 eV [23] or Na 3 O 3.13 eV vs. Na 4 O…”
Section: Introductionmentioning
confidence: 99%